1997
DOI: 10.1007/s002280050237
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study and cardiovascular monitoring of nebivolol in normal and obese subjects

Abstract: The distribution of nebivolol in the adipose tissue in obese subjects is limited, despite its high lipophilicity. The differences between obese and non-obese subjects were not clinically relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 9 publications
3
24
1
3
Order By: Relevance
“…The results of pharmacokinetic studies for the healthy controls were similar to those reported by other investigators [11][12][13]. In obese subjects both with and without hyperlipidaemia the pharmacokinetics of propranolol and atenolol were altered, most significantly during the elimination phases.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of pharmacokinetic studies for the healthy controls were similar to those reported by other investigators [11][12][13]. In obese subjects both with and without hyperlipidaemia the pharmacokinetics of propranolol and atenolol were altered, most significantly during the elimination phases.…”
Section: Discussionsupporting
confidence: 87%
“…Contrary to our observations, Cheymol et al [12] reported an increased clearance of nebivolol in obesity. Nevertheless, the results of Galletti et al [11] suggested that obesity did not influence the pharmacokinetics of water-soluble b-blockers.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…110 However, in poor metabolizers taking metoprolol, the lower S/R ratio leads to less ␤-blockade relative to plasma levels, 111 which tends to cancel the effect of the increased plasma levels of both isomers that is related to the lower oxidation rate. Clinically important stereoselective metabolism does not occur for bisoprolol, 112 nebivolol, 113 or bucindolol (D. Ward, personal communication, 1999).…”
Section: Pharmacokinetic Issuesmentioning
confidence: 99%
“…The decrease in CYP2D6 activity in human hepatocytes with excess fat may be due to a decreased mRNA level of this gene. On the contrary, Cheymol et al 42 showed increased CYP2D6 activity in obese subjects; nebivolol was used as a CYP2D6 substrate.…”
Section: Subfamily Of the Cyp2d Enzymementioning
confidence: 99%